Investigating the relative adsorption of polymeric depressants on pure minerals - Mhlanga, Sabatha Sanele (Department of Chemical Engineering, 2015)
The aim of this study was to investigate the relative adsorption of polymeric depressants on pure minerals. The minerals used were talc, pyroxene, plagioclase, chromite and chalcopyrite and the depressants used were guar gum and carboxymethyl cellulose (CMC). It was hypothesised at the beginning of this study that polymeric depressants adsorb preferentially onto different minerals because of the differences in the surface charge of the minerals which arise as a result of their different chemical structures. Zeta potential measurements were conducted to establish exactly what these differences in surface charge were and what role metal ions in solution played in modifying the mineral surface charge and therefore changing the adsorption characteristics.